ILLEGAL FORMATION (CREATION, REORGANIZATION) OF A JURIDICAL PERSON: ISSUES OF QUALIFICATION AND LEGAL REGULATION OF LIABILITY - N. A. Egorova; A. A. Likholetov (Russian Journal of Economics and Law, 2015)
Objective: to analyze the disposition of part 1 of Article 173.1 of the Russian Criminal Code and comments to this Article, to identify their shortcomings; to consider problems of practical application of Article 173.1 and to formulate proposals on legislation improvement aimed at increasing the efficiency of counteraction to illegal formation of a juridical person. Methods: a combination of general scientific (induction, deduction, analysis and synthesis) and specific scientific (formal-legal, comparative legal, sociological, content analysis) methods. Results: the paper proposes an analysis of Article 173.1 of the Criminal Code and the current state of law enforcement practice on criminal cases concerning the illegal formation (creation, reorganization) of a juridical person. Basing on empirical material, the authors show the problems in classification of these crimes. The authors conclude that the unsatisfactory results of the struggle against "short-lived" companies result mainly from the imperfection of the existing criminal law, and prove the need for decriminalization of these crimes, simultaneously establishing administrative liability for such acts and excepting Article 173.1 from the Criminal Code or changing its content. Scientific novelty: basing on the existing legal norms, modern scientific literature on the topic, and materials on applying Article 173.1 of the Russian Criminal Code, the article studies the signs of illegal formation (creation, reorganization) of a juridical person, which cause the greatest difficulties in the crime qualification, and sets out the author's proposals on legislation improvement, in particular, an exemplary article of the Administrative Code of the Russian Federation on formation (creation, reorganization) of "short-lived” companies. Practical value: the judgments and conclusions contained in the article can be used in law-making activities (for the development of draft laws on introducing changes and amendments to the criminal and administrative law), in the law-enforcement practice (for the qualification of crimes in the sphere of economic activity), in the scientific research (preparation of theses, monographs, textbooks, scientific articles), in the educational process (teaching the discipline "Criminal law” and special courses on criminal law).